Home Computer Use and Shifts in Family's Time-Allocation Patterns - Brahim, Ismail (1997)
The Malaysian government's serious commitment to make computers more accessible to all would mean more personal computers are expected to move into the Malaysian homes. Since computers are effective time consuming devices which force users to reallocate their limited time for doing various activities, computing particularly in the home, has the potential to change the way family members interact with each other. However, despite the increasing importance of computers, little attention seems to have been paid towards understanding computer use in relation to the household. This study was conducted specifically to determine (1) the characteristics of home computer users, (2) the relationships between shifts in family's time-allocation patterns and indicators of computer use (actual time spent on home computing, frequency of computer use, and number of software packages used), and (3) the relationship between home computing and family communication. This study was conducted on active computer users, representing the principal users of family computers, on Internet services and other software packages, and/or both packages. A total of 109 individuals from the Klang Valley participated in this study. Data were collected through self-administered mail questionnaires and analyzed by using statistical analyses, such as, frequencies, means, medians, standard deviations, percentages, Chi-square, and Spearman Rank-Order Correlation, by means of SPSS-WIN computer program. The findings showed that home computer/Internet users were middle aged, well-educated professional managerial workers, males, heading average size households with high annual income. Shifts in time-allocation patterns for eight activities were negatively related to time spent on home computing, frequency of computer use, number of software packages used, and overall home computer use. Time spent for taking family members to various services; time spent for sleeping; time for hobbies; time with friends; and time spent for using other media, that is, for watching television, listening to radio, reading newspapers, and reading books, were significantly reduced. The amount of communication in the family was found to be positively related to the time spent and frequency of computer use, suggesting that using the family computer had enhanced communication among family members. However, home computing had only occasionally helped family members communicate more effectively and achieved desirable communication environment in the family_ Based on the findings of this study, there is a need for family members to reallocate time and reprioritize household activities to satisfy the family's basic demands and functioning, and be able to cope with the increasing social implications of the technological innovations in communication.